Pengaruh Penambahan Tepung Ubi Jalar dalam Pakan Lokal Terfermentasi Terhadap Performance Ternak Babi Duroc Fase Grower di Desa Turekisa - Dua, Kresensia Mariana; Sampe, Yulius A.G.; Noywuli, Nicolaus (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to determine the effect of adding sweet potato flour (Ipomoea batatas) in fermented local feed on the performance of Duroc pigs in the grower phase. Sweet potato is a potential source of carbohydrates with nutritional content that supports livestock growth, while fermentation of local feed aims to increase the digestibility and availability of nutrients. In general, people in Turekisa village raise pigs to meet economic needs, therefore optimal pig production requires good nutrition. This study used an experimental design with two treatments on the addition of sweet potato flour in feed, namely 100% fermented local feed in treatment 0 (P0) and 10% sweet potato flour in treatment 1 (P1). The parameters observed included consumption, body weight gain (PBB) and feed conversion, feed efficiency, and general livestock health. The results showed that the addition of sweet potato flour in fermented local feed significantly increased (PBB) and feed efficiency at an addition level of up to 10%. In addition, fermentation of local feed had a positive impact on the digestibility of crude fiber and the availability of metabolic energy. The conclusion of this study is that the addition of sweet potato flour up to 10% in fermented local feed can improve the performance of Duroc pigs in the grower phase. This study provides practical implications for the development of more economical and environmentally friendly local-based feed for pig farming